Albedo factor determination of rare-earth oxides - Turşucu, Ahmet (RADIATION EFFECTS AND DEFECTS IN SOLIDS, 2018)
Gamma-ray albedo factors of rare-earth oxides were determined experimentally. The detection of albedo factors for selected materials includes albedo number, albedo energy and albedo dose calculations. 59.54 keV gamma rays of 5 Ci annular Am-241 were used as a gamma source. Gamma rays were scattered by selected samples and collected by High Purity Germanium semiconductor detector. The albedo factors were plotted as a function of atomic number of target materials.
Keywords: Gamma ray scattering; Albedo factors; Albedo number; Albedo energy; Albedo dose